2019
DOI: 10.1111/bjh.15803
|View full text |Cite
|
Sign up to set email alerts
|

Romiplostim in adult patients with newly diagnosed or persistent immune thrombocytopenia (ITP) for up to 1 year and in those with chronic ITP for more than 1 year: a subgroup analysis of integrated data from completed romiplostim studies

Abstract: Summary The thrombopoietin receptor agonist romiplostim is approved for second‐line use in chronic immune thrombocytopenia (ITP), but its effects in patients with ITP for ≤1 year are not well characterized. This analysis of pooled data from 9 studies included patients with ITP for ≤1 year (n = 311) or >1 year (n = 726) who failed first‐line treatments and received romiplostim, placebo or standard of care. In subgroup analysis by ITP duration, patient incidences for platelet response at ≥75% of measurements wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 36 publications
8
66
1
4
Order By: Relevance
“…[52][53][54] Consensusbased recommendations for patients with ITP undergoing surgery are presented in Table 6. and death in patients older than 60 years), [55][56][57][58] patients with other comorbidities, or those on anticoagulants. Depending on a treatment response, the most appropriate additional treatments should be selected, treatment side effects should be minimized, and patients should be selected for further treatment as needed.…”
Section: Who Should Be Treated?mentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54] Consensusbased recommendations for patients with ITP undergoing surgery are presented in Table 6. and death in patients older than 60 years), [55][56][57][58] patients with other comorbidities, or those on anticoagulants. Depending on a treatment response, the most appropriate additional treatments should be selected, treatment side effects should be minimized, and patients should be selected for further treatment as needed.…”
Section: Who Should Be Treated?mentioning
confidence: 99%
“…123 However, there is some evidence that thrombotic events are higher in ITP patients on romiplostim, especially those older than 60 years. 56 ROMIPLOSTIM. Many studies on romiplostim have been published (evidence levels Ib, IIb, and III).…”
Section: Subsequent Therapy: Medicalmentioning
confidence: 99%
“…Systematic review of trials examining clinical thromboembolic events has found higher rates in patients on TPO‐RAs compared with controls, 5 and a long‐term clinical study of eltrombopag showed 6% of patients developed arterial or venous thrombosis 34 . There are similar findings with romiplostim, but direct comparison with placebo showed no increase in thrombotic risk; 6,18 however, as expected, risk of thrombosis increases with age 18 …”
Section: Management Of New/relapsed Itpmentioning
confidence: 99%
“…Only recently has this been changed for eltrombopag, which is now indicated for patients with primary ITP lasting 6 months or longer from diagnosis and who are refractory to other treatments [16]. Retrospective studies have shown that the use of TPO-RAs in the treatment of patients with newly diagnosed ITP in daily clinical practice is as effective and safe as it is in chronic ITP [17,18] and an ongoing clinical trial is currently evaluating this line of treatment in children (NCT03939637). Therefore, more changes in clinical treatment methods are to be expected in the future and further real-world studies are needed to depict the changing clinical treatment landscape.…”
Section: %mentioning
confidence: 99%